Selection of tannase-producing Aspergillus niger strains - Pinto,Gustavo A.S. (2001)
The aim of this work was to select strains of Aspergillus niger for tannase production. Growth of colonies in plates with tannic acid-containing medium indicated their ability to synthesize tannase. Tannase activity was also measured in solid-state fermentation. A. niger 11T25A5 was the best tannase producer (67.5 U.g-1/72 hours of fermentation).